Caesarean Section Delivery and Risk of Poor Childhood Growth - Mahama Saaka; Addae Yaw Hammond (Journal of Nutrition and Metabolism)
Background. Though emerging evidence indicates caesarean section (CS) brings about late initiation of breastfeeding, early cessation of breastfeeding, and a higher risk of developing obesity, little is documented on the association between CS birth and stunted growth. This study assessed caesarean section delivery and the risk of poor postnatal childhood growth. Methods. A retrospective cohort study design was used to collect the requisite data on a sample of 528 mothers having children between the ages of 6 to 24 months. An interviewer-administered questionnaire was used to collect the data. Results. After controlling for potential confounding factors, linear growth as measured by height-for-age Z-score (HAZ) was significantly higher by 0.121 standard units in children born through normal vaginal delivery, compared to their counterparts born through caesarean section (beta coefficients (β) = 0.121, p=0.002). The mode of delivery also had a statistically significant impact on infant feeding practices. Whereas 70.4% of babies delivered via vagina initiated breastfeeding within one hour of delivery, only 52.7% of babies born through CS did the same. Vaginally delivered babies were 2.1 times more likely to initiate breastfeeding within one hour of delivery ((Crude odds ratio (COR) = 2.13, p<0.001). Compared to CS babies, vaginally delivered babies were 3.2 times more likely not to have been fed with prelacteal feeds such as water and sugar solutions. Vagina delivered babies were 1.8 times more likely to receive adequate neonatal feeding than their counterparts who were delivered through CS (COR = 1.76, p=0.003). Conclusions. This study has found an association between CS delivery and stunting, an adverse outcome that clinicians and patients should weigh when considering in particular elective CS that seeks to avoid the pain associated with a vaginal birth.